Training Needs of Women Dairy Farmers in AL Saniya District, AL Qadisyah Province, Iraq. - Bassim Haleem Kshash; Hayat Oda (Journal of Agricultural Extension, 2019)
Any increase in milk production depends on effective use and  application of improved dairy farming practices which requires some changes in knowledge and skills of dairy farm womenâ€™s that can reached by training . The study was conducted in AL Qadisyah Province, Iraq. A sample of 125 farm women was selected through random sampling. Face-to-faces interviews with a structured questionnaire were used to collect data. The majority of respondents (61.6%) had a medium level of training needs on some dairy farming practices followed by high (26.4%) and low (12%) levels of training needs. Health  care is the most preferred training aspect of farm women followed by feeding, clean milk production, breeding and marketing, while care and management of milking  animals, disease Prevention, feeding of milk animals, and  preparation of milk products the most preferred training sup aspect. The study recommends that improved dairy farming practices  should be diffuse and application by dairy farm womenâ€™s .